Video Head Impulse Test in Darkness, Without Visual Fixation: A Study on Healthy Subjects - Pérez-Vázquez, Paz; Franco-Gutiérrez, Virginia (Ear and hearing, 2022)
The head impulse test (HIT) is triggered by the vestibulo-ocular reflex (VOR), complemented by the optokinetic and pursuit systems. This study aimed to evaluate the possibility of individualizing the VOR contribution to the HIT. Thirty-six healthy individuals (19 males, 17 females; age 21-64 years, mean 39 years) underwent horizontal video HIT (vHIT). This was first conducted in darkness, without visual fixation, and then visually tracked. Seventy percent of the impulses delivered ocular responses opposite to the direction of the head, matching its velocity to a point where quick anticompensatory eye movements (SQEM) stopped the response (SQEM mean latency 58.21 ms, interquartile range 50-67 ms). Of these, 75% recaptured the head velocity after culmination. Thirty percent of the responses completed a bell-shaped curve. The completed bell-shaped curve gains and instantaneous gains (at 40, 60, and 80 ms) before SQEM were equivalent for both paradigms. Females completed more bell-shaped traces (42%) than males (15%); p = 0.01. The SQEM latency was longer (62.81 versus 55.71 ms, p < 0.01), and the time to recapture the bell-shaped curve was shorter (77.51 versus 92.52 ms, p < 0.01) in females than in males. The gains were comparable between sexes in both paradigms. The VOR effect can be localized in the first 70 ms of the vHIT response. In addition, other influences may take place in estimating the vHIT responses. The study of these influences might provide useful information that can be applied to patient management.